Development of Aluminium 6082 alloy reinforced with Al2O3 by die casting and investigation of microstructural and mechanical properties. (2020) - Lukose, Laiju; Babu, Kumaresh; Srinivasan, S.A.
Abstract: The present work is focused on developing AMC composites by using Al-6082 as base matrix alloy and Alumina particles as reinforcement. The mechanical properties of Al-6082 can be enhanced by grain refinement caused by Alumina. The permanent die casting method was used for the synthesis of Al-6082 – Alumina composite due to its cost effectiveness and simplicity. It will also help to study the influence of rate of solidification in the microstructure of the composite. The reinforcement is added in various weight proportions to the matrix. The variations in the microstructural and mechanical properties was observed for composites with varying proportions of Al2 O3 . The mechanical properties was studied using micro tensile test, density test and Vickers hardness test, The microstructural properties was analysed using characterization techniques such as optical emission spectroscopy, optical microscopy, SEM with EDS and elemental mapping. It seems that the mechanical properties are improving and stabilizing when the reinforcement addition is approaches 3% by weight. The ultimate tensile strength has highest values for composite having 2% by weight of reinforcement. The improvement in mechanical properties has been observed in the base alloy after addition of Al2 O3 could be attributed with the grain morphology. Grain refinement is occurring in all the three dimensions with increasing percentage of reinforcement and fine grain structure is obtained for AMC with 3% reinforcement. The reduction in tensile strength may be due to the agglomeration of ceramic reinforcement particles. The result shows the promising trend which can be utilized for further heat treatment studies, corrosion studies and tribological studies on which suggestions can be provided for employing the same in various engineering applications.